KNOWLEDGE, ATTITUDE, AND PRACTICE REGARDING MENSTRUAL HYGIENE IN FEMALE ADOLESCENTS - BASHARAT , J; SADDIQUE , H; TASNEEM , SS (Biological and Clinical Sciences Research Journal, 2024)
Menstrual hygiene is a critical aspect of adolescent health and well-being. However, cultural taboos, lack of education, and limited resources contribute to poor menstrual hygiene management (MHM), particularly in developing countries like Pakistan. Objective: To assess the knowledge, attitudes, and practices (KAP) regarding menstrual hygiene among female adolescents in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 172 female adolescents aged 12–18 years. Data were collected using a structured questionnaire covering socio-demographic characteristics, knowledge, attitudes, and practices related to menstrual hygiene. Descriptive and inferential statistics were analyzed using SPSS version 26.Results: The study found that 45.3% of participants had low knowledge of menstrual hygiene, 59.3% exhibited negative attitudes, and 65.1% demonstrated poor practices. Parents were the primary source of information (72.7%), while schools and healthcare providers played a minimal role. Common misconceptions and suboptimal practices, such as reusing cloth, highlighted the urgent need for education and awareness. Conclusion: Despite some awareness, significant gaps in knowledge, negative attitudes, and unsafe practices prevail among female adolescents in Lahore. Comprehensive educational programs involving families, schools, and healthcare providers are essential to improve menstrual hygiene management and empower adolescent girls to manage menstruation safely and with dignity.